MENGEMBANGKAN KEMANDIRIAN MELALUI MEDIA FILM ANIMASI “UPIN DAN IPIN” PADA ANAK DIDIK KELOMPOK B TK WAHIDIYAH KECAMATAN MOJOROTO KOTA KEDIRI - Danang Prastyo (Universitas Al-Hikmah Indonesia, 2022)
This Classroom Action Research was conducted on group B students in kindergarten. Wahidiyah Kediri City. The research is based on the observations and experiences of researchers, that the independence of students is still very low. The problem of this research is